A Proposal to Refer to Four Coronaviruses of Limited Human Virulence "Common Cold Coronaviruses". (2nd September 2022) - McIntosh, Kenneth; Perlman, Stanley; Monto, Arnold; Englund, Janet A
Summary: We propose the term "common cold coronaviruses, " or ccCoV, to describe the four human coronaviruses commonly associated with upper respiratory tract disease – coronaviruses 229E, OC43, NL63, and HKU1. This will differentiate these previously described coronaviruses from those causing more severe disease in humans – including the viruses severe acute respiraotry syndrome coronavirus (SARS-CoV), the Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV-2. Abstract : We propose the term "common cold coronaviruses, " or ccCoVs, to describe the 4 human coronaviruses commonly associated with upper respiratory tract disease (coronaviruses 229E, OC43, NL63, and HKU1).